Phase III, Randomized, Placebo-Controlled Trial of CC-486 (Oral Azacitidine) in Patients With Lower-Risk Myelodysplastic Syndromes. Issue 13 (1st May 2021) - Garcia-Manero, Guillermo; Santini, Valeria; Almeida, Antonio; Platzbecker, Uwe; Jonasova, Anna; Silverman, Lewis R.; Falantes, Jose; Reda, Gianluigi; Buccisano, Francesco; Fenaux, Pierre; Buckstein, Rena; Diez Campelo, Maria; et al.
Abstract : PURPOSE: Treatment options are limited for patients with lower-risk myelodysplastic syndromes (LR-MDS). This phase III, placebo-controlled trial evaluated CC-486 (oral azacitidine), a hypomethylating agent, in patients with International Prognostic Scoring System LR-MDS and RBC transfusion–dependent anemia and thrombocytopenia. METHODS: Patients were randomly assigned 1:1 to CC-486 300-mg or placebo for 21 days/28-day cycle. The primary end point was RBC transfusion independence (TI). RESULTS: Two hundred sixteen patients received CC-486 (n = 107) or placebo (n = 109). The median age was 74 years, median platelet count was 25 × 10 9 /L, and absolute neutrophil count was 1.3 × 10 9 /L. In the CC-486 and placebo arms, 31% and 11% of patients, respectively, achieved RBC-TI ( P = .0002), with median durations of 11.1 and 5.0 months. Reductions of ≥ 4 RBC units were attained by 42.1% and 30.6% of patients, respectively, with median durations of 10.0 and 2.3 months, and more CC-486 patients had ≥ 1.5 g/dL hemoglobin increases from baseline (23.4% v 4.6%). Platelet hematologic improvement rate was higher with CC-486 (24.3% v 6.5%). Underpowered interim overall survival analysis showed no difference between CC-486 and placebo (median, 17.3 v 16.2 months; P = .96). Low-grade GI events were the most common adverse events in both arms. In the CC-486 and placebo arms, 90% and 73% of patients experienced a grade 3-4 adverse event. Overall death rate was similar between arms, but there was an imbalance in deaths during the first 56 days (CC-486, n = 16; placebo, n = 6), most related to infections; the median pretreatment absolute neutrophil count for the 16 CC-486 patients was 0.57 × 10 9 /L. CONCLUSION: CC-486 significantly improved RBC-TI rate and induced durable bilineage improvements in patients with LR-MDS and high-risk disease features. More early deaths occurred in the CC-486 arm, most related to infections in patients with significant pretreatment neutropenia. Further evaluation of CC-486 in MDS is needed.